Design-Driven Sustainable Business Model Innovation: The Case of the Malaysian Furniture Industry - Wan Zaiyana Mohd Yusof; Puteri Fadzline Muhamad Tamyez; Rahamaddulla Syed Radzi; Dato' Hasnah Hj Haron (Intellect, 2026)
Tier 2 (Indexed by SCOPUS)